Efeito da urbanização sobre assimetria das asas de Jataí (Tetragonisca angustula - Hymenoptera: Apidae: Meliponini) - ANA PAULA VALDEZ ANDREAZZI (2023)
Tetragonisca angustula bees are widely distributed throughout Brazil and are crucial indicators of environmental quality and preservation. Despite their adaptive capacity to urban environments, these bees still face potential negative impacts of urbanization. The presence of T. angustula in urban areas may produces effects in wing morphology and asymmetry due to human influence, such as alterations in landscape, temperature, and plant diversity. Morphometrical methods and statistical analyses are crucial tools in comprehending these morphological variations. This study aims to investigate the environmental effects on wing asymmetry in T. angustula bees along an urban gradient, expecting an increase in asymmetry in unfavorable urbanized environments, as well as variations in wings geometric morphometrics, determining if it occurs, in which places and in what extention. We evaluated three distinct locations: an urban zone, a suburban natural region, and a rural natural area. Employing geometric morphometrics, we analyzed 160 individuals, 320 wings, and 8 anatomical landmarks per wing. The anatomical landmarks were transformed using the Procrustes technique, and the degree of asymmetry for each wing was calculated considering the difference in the mean of the anatomical landmarks. For comparison among the three areas, an analysis of variance was conducted. To establish the morphometric variations, principal component analysis was used, along with multivariate analysis of variance for comparison between areas, and deformation grids concerning the centroids of each anatomical landmark. The results unveiled different asymmetry patterns, supporting the hypothesis that urban areas are more asymmetric compared to the other two areas, and that urbanization more profoundly affects the wing morphometrics of the species' anatomical landmarks, indicating possible influences of food resources, temperature, and ecological pressures in these variations. Keywords: Native bee, Fluctuating asymmetry, Geometric morphometrics